Bioaccumulation and Toxicity of Copper and Lead in Chlorella vulgaris - Regaldo, Luciana María; Gervasio, Susana Graciela; Troiani, Horacio Esteban; Gagneten, Ana María (Phycospectrum, 2013)
Fil: Regaldo, Luciana María. Universidad Nacional del Litoral. Facultad de Humanidades y Ciencias; Argentina